CHANGES IN SALT COMPOSITION OF OIL CONTAMINATED BLACK SOILS - Aleksey А. Buluktaev (Юг России: экология, развитие, 2018)
Aim. The Republic of Kalmykia is rich in fossils minerals, the main of which are oil, gas, condensate, etc. The republic includes three main morphostructures: the Caspian lowland, the Ergeninskaya Upland and the Kuma-Manych depression. The Caspian lowland, in turn, is divided into the Sarpinskaya lowland and the Black Lands. Practically all hydrocarbon production fields are concentrated in the territory of the Black Lands. In this regard, the most acute for this area are issues of environmental management and problems associated with the seepage of petroleum products into the environment. In the present work, was investigated the problem of soil contamination within the Nadezhdinsky, North-Kamyshansky, Tengutinsky, Bairskoye and Sostinsky oil deposits. Methods. The soil composition of the deposits is due to the complexity and is characterized by a light granulometric composition and, in most cases, salinity. The soils were analyzed for the content of Са2+, Mg2+ and Na+ cations, НСО3- , CI- and SO42 anions as well as their pH values. Results. Contamination of soils with oil and petroleum products leads to deterioration of its physical and chemical properties, salinity increase, soil alkalinization; soils saturated with oil products, lose the ability to retain moisture, they are characterized by lower values of hygroscopic moisture, water permeability and moisture capacity. Conclusions. The study revealed that the oil pollution of the Black Lands leads to a change in the quality of salinity; the content of sodium and chlorine ions increases in the oil-contaminated soils.